Future of Agriculture under Climate Change and its Impact on Agricultural Production, Food Security, and Sustainable Adaptation Strategies - Ibrahem Adnan Al-Taee; Zakariya Ahmed Hussein; Mohammed Jamal Hadi; Mohammed Khalil Taha; Sabir Talib Sabir; Eder Dawood Shlemun; Muna Hashim Taha/Al-Azzawi (American Journal of Biology and Natural Sciences, 2026)
Climate change is one of the key issues that face the agricultural systems and food security in the twenty-first century all over the world. The current research aims to analyze effects of climate change on agriculture, especially on crop production, water, soil degradation as well as interaction of pests and dise. The paper clarifies the negative effects of the high temperature, changes in the patterns of precipitation, and the rising numbers of the extreme weather conditions on the agricultural sector, thus threatening the food supply, access, and stability. The paper also examines the build of pressure on water resources whereby irrigation systems and the effectiveness of water use under the climate-stressed conditions play a central role. Adaptation and mitigation, such as climate-smart agriculture, sustainable agricultural methods, planting of climate-resilient varieties of crops and incorporation of renewable energy into agricultural systems are also addressed in the manuscript. The future outlook of agriculture is assessed with regards to the technological progress, precision farming, as well as the role of governmental and institutional assistance in the development of sustainable agricultural growth. It has been found that comprehensive and preventive measures are necessary to improve agricultural resilience, reduce exposure to climatic perturbations, and guarantee long-term food security. To sum up, research, policy frameworks, and investment in sustainable agricultural practices should be increased to build resilient food systems amidst the changing climatic conditions.